Novel cystogenic role of basic fibroblast growth factor in developing rodent kidneys - Li, Zhuangwu; Jerebtsova, Marina; Liu, Xue-Hui; Tang, Pingtao; Ray, Patricio E. (American journal of physiology. Renal physiology, 2006)
Basic fibroblast growth factor (bFGF) is a heparin-binding growth factor that is accumulated in human dysplastic and cystic renal diseases. Previous studies have shown that bFGF can modulate the growth of developing renal tubules; however, its role in the pathogenesis of renal cyst formation is not clearly understood. Here, we tested the hypothesis that overexpression of bFGF in developing rodent kidneys induces cyst formation in vivo. We used two different adenoviral-mediated gene-transferring approaches to overexpress bFGF in developing rodent kidneys. Initially, metanephric kidney (MK) explants harvested from embryonic day 15 Sprague-Dawley rats were infected with adenoviral vectors (rAd) encoding human bFGF or LacZ genes and transplanted under the renal capsule of adult female rats. Subsequently, to determine whether bFGF could induce renal cysts in developing kidneys with an intact renal collecting system, we injected rAd-bFGF or LacZ vectors in the retroorbital plexus of newborn mice. Basic FGF induced a more efficient integration of the MK explants into the host kidneys and increased the vascularization and proliferation of developing tubules, leading to tubular dilatation and rapid formation of renal cysts. In addition, we successfully expressed human bFGF in the kidney of newborn mice in vivo and induced tubular dilatation and renal cysts. In contrast, mice injected with rAd- lacZ did not develop tubular dilatation or renal cysts. To the best of our knowledge, these experiments show for the first time that overexpression of bFGF in developing rodent kidneys can induce the formation of renal cysts in vivo.